Reflecting on the Anthropocene: The Call for Deeper Transformations: This article belongs to Ambio’s 50th Anniversary Collection. Theme: Anthropocene - O’Brien, Karen (Ambio, 2021)
Research on global environmental change has transformed the way that we think about human-environment relationships and Earth system processes. The four Ambio articles highlighted in this 50th Anniversary Issue have influenced the cultural narrative on environmental change, highlighting concepts such as “resilience,” “coupled human and natural systems”, and the “Anthropocene.” In this peer response, I argue that global change research is still paying insufficient attention to how to deliberately transform systems and cultures to avoid the risks that science itself has warned us about. In particular, global change research has failed to adequately integrate the subjective realm of meaning making into both understanding and action. Although this has been an implicit subtext in global change research, it is time to fully integrate research from the social sciences and environmental humanities.